POTENSI RIZOBAKTERI PEMBENTUK ENDOSPORA DARI TANAMAN PADI SEBAGAI BIOKONTROL FITOPATOGEN Xanthomonas oryzae - Maerani Sumarno; Anto Budiharjo; Sri pujiyanto (Jurnal Akademika Biologi, 2014)
Xanthomonas oryzae is phytopathogen causing bacterial leaf blight which decreases in agricultural product reaching 20-70 % in Asia. Bacterial leaf blight symptoms is characterized by the formation of lines in the leaf blade turnings yellow, then white, causing the plant to wither and die. Endospore-forming rhizobacteria are soil microbes potential as biocontrol to inhibit phytopathogen growth. The aims of this study were to isolate endospore-forming rhizobacteria from rice plant and determine its ability as biocontrol against X. oryzae. The methods used consisted of isolation, antibacterial activity test, molecular identification, and biochemical characterization. Twenty isolates of endospore-forming rhizobacteria were obtained from the isolation of the rice crop. Isolate P-10 had the greatest ability against X. oryzae with inhibition zone of 18.89 mm. Molecular identification using 16S rRNA gene showed that isolates P-10 had 98 % homology with Bacillus pumilus. Biochemical characterization showed the isolate P-10 had a rod-shaped with center of endospores, gram-positive, catalase positive, are motile, negative in starch hydrolyze, not forming gas on glucose, these characteristics fitted with B. pumilus character. Keywords : Rice plant, antibacterial, Xanthomonas oryzae, endospore-forming, rhizobacteria